Caste Reform in Early 20th Century India: The Contributions of Shahu Maharaja to Social Equality (International Journal of Food and Nutritional Sciences, 2020)
The early 20th century in India witnessed significant social reform movements aimed at dismantling the entrenched caste system, with Shahu Maharaja of Kolhapur emerging as a pivotal figure in this transformation. This research explores Shahu Maharaja’s role in caste reform, focusing on his religious thoughts, educational policies, and socio-religious actions. Despite his conservative Hindu upbringing, Shahu Maharaja evolved into a progressive reformer, advocating for an egalitarian society that transcended traditional caste boundaries. His approach to religious reform challenged the rigid Brahminical hegemony, promoting a vision of religious and social equality. This study examines Shahu Maharaja’s rationale for these reforms, his innovative policies including the creation of a Kshatriya high priest, and his strategies to integrate non-Brahmins into the socio-religious fabric of his state. By critically analyzing his contributions, this research highlights Shahu Maharaja’s impact on the trajectory of social equality in early 20th-century India.